Are workers in the cultural industries paid differently? - Cecile Wetzels (Institute for the Study of Labor (IZA), 2007)
This paper aims to explore wage differentials between employees in three sub-industries of the cultural industries compared with the main (1-digit level) industry to which they belong. We use data from the Wage Indicator Questionnaire 2001/2002, which includes information on 12,757 employees in the Netherlands. We find that workers in these particular sub-industries of the cultural industries are paid differently compared with their respective main industries. Workers in entertainment and publishing and printing are less endowed with standard labour market characteristics. However, whereas workers in entertainment face negative price or evaluation-related effects, the opposite holds for workers in publishing and printing. Workers in IT are more endowed with standard labour market characteristics, but they receive lower rewards for their labour market characteristics.
urn:nbn:de:101:1-20080328130
Keywords: 330; Lohnstruktur; Freizeitwirtschaft; Verlagsgewerbe; EDV-Dienstleistung; Kultursektor; Niederlande